HUBUNGAN INFORMASI NON-AKUNTANSI DALAM PROSPEKTUS DENGAN TINGKAT INITIAL RETURN DI BURSA EFEK JAKARTA:BUKTI LANJUTAN - Tatang Ary Gumanti; Sri Indah Cahyati (Akutansi Bisnis & Manajemen ( ABM ), 2002)
This study examines the association between the firms? initial return and non-accounting information available in the issue of prospectus of an initial public offerings (IPO) in the Jakarta Stock Exchange. Five non-accounting information were examined. These include reputation of underwriters, reputation of auditor, company age, the percentage of retained ownership, and the value of the issue. A sample of 86 IPO firms that went public during the period of 1992-1995 was tested. An ordinary least square (OLS) regression was used to test the null hypothesis that the non-accounting information available in the issue prospectus is not related to the IPO?s initial return. Initial return was measured as the relative difference between the firm?s first day closing price and its offer price. Two measures of initial returns were examined: (1) initial return that does not incorporate the market return, that is the raw initial return, and (2) initial return adjusted for the market return, that is market adjusted initial return. Reputation of underwriters, reputation of auditors, company age, and offering value were expected to be negatively associated with initial returns. Retained ownership is predicted to have positif relationship. The results show that non-accounting information of prospectus is significantly associated with IPO initial returns meaning that the null hypothesis is rejected. The reputation of underwriters has a positive association with initial returns. Auditor reputation, retained ownership and the size of the issue have the expected relationship, but the relation between company age and initial return is positive. Only the size of issue is significantly related to the level of initial return. The results using market adjusted return produce qualitatively similar conclusions as that using raw initial return. Overall, the finding suggests that in making decision in the new issue stock, investors are encouraged to consider non-accounting information of prospectus in particular the size of the issue.